2008
DOI: 10.1142/s1084946708000910
|View full text |Cite
|
Sign up to set email alerts
|

Financial Funding of Immigrant Businesses

Abstract: This study investigates differences in financial funding between immigrant and non-immigrant businesses and delineates factors influencing financial funding of immigrant businesses. Data for the study were collected in Israel between 2000 and 2005. By combining convenient and snowball samples, 214 native Israelis and 153 FSU immigrant entrepreneurs answered a questionnaire. We classified financial sources for immigrant businesses according to their affiliation to the ethnic community, and according to their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 11 publications
1
43
0
Order By: Relevance
“…Although Kushnirovich and Heilbrunn (2008) emphasised access to own start-up capital, Basu (1998) found a strong relation between own savings (personal capital) plus the share of informal capital in the start-up, on one hand, and the success of the business, on the other hand. Cavalluzzo and Wolken (2005) suggested that personal wealth and credit history are possible explanations for the differences in receiving bank loans.…”
Section: Owner Characteristicsmentioning
confidence: 99%
“…Although Kushnirovich and Heilbrunn (2008) emphasised access to own start-up capital, Basu (1998) found a strong relation between own savings (personal capital) plus the share of informal capital in the start-up, on one hand, and the success of the business, on the other hand. Cavalluzzo and Wolken (2005) suggested that personal wealth and credit history are possible explanations for the differences in receiving bank loans.…”
Section: Owner Characteristicsmentioning
confidence: 99%
“…As they are not experimental audit studies, they are unable to create a random sample of observationally equivalent small business borrowers that differ only in their race. While not analyzing whether the entrepreneur was denied or granted credit, Marlow and Patton (2005) study female entrepreneurs in the United Kingdom, Kushnirovich and Heilbrunn (2008) study immigrants in Israel, Sepulveda et al (2011) study the "superdiverse" migrant enterprises within London, Haynes et al (2008) study the sources of financing for Mexican-American and Korean-American borrowers, and Aldrich and Zimmer (1986) argue for an evolutionary population perspective for successful entrepreneurship. Additionally, even after including the social capital and liability of newness measures 12 of Bewaji et al (2015), I still find evidence that African-American borrowers have a higher probability of their loan being rejected than equivalent risk white borrowers.…”
Section: B Empirical Studies Of Discriminationmentioning
confidence: 99%
“…While immigrant entrepreneurs contribute significantly to job creation and innovation in the United States, they generally face greater challenges in acquiring financial capital than do their mainstream peers (Kushnirovich and Heilbrunn, ). The literature on sociology (Aldrich and Waldinger, ; Fisman, ; Nielsen, ) and entrepreneurship (Bates, ; Brüderl and Preisendörfer, ; Masurel et al, ) have long recognized the importance of the social network of co‐ethnics in funding new businesses.…”
Section: Introductionmentioning
confidence: 99%